„Jesteśmy blisko i coraz więcej o sobie wiemy”. Komentarz do bibliografii za lata 2007—2013 - Żygadło-Czopnik, Dorota (Przekłady Literatur Słowiańskich, 2014)
„We are close and we know more and more about each other”. A commentary to the bibliography for the years 2007—2013 The discussed here bibliography for the years 2007—2013 is without any doubt one of the most important publications on the subject of translations into Czech and Polish languages. The retrospective bibliography is a very good source for bibliographical information about Polish and Czech literature translation in the years 2007—2013, as well as for the Polish and Czech writing in general. The publication includes a bibliography which makes an attempt to present, if it’s possible, a full picture of the book and periodical production, which were published on the territories of Poland and the Czech Republic. The translations bibliography constitutes a general material for an overview of the development of the Czech and Polish prose, poetry and drama in the recent years. It can be said that we are richer for a book, in which the author was able to elaborate on the development of the translating activity in Poland and the Czech Republic. This work proves to be valuable not only for the highly specialized experts in the fields of philology and literary history, who have now an access to a comprehensive overview of the Czech and Polish literature in translation, but also is a great introductory material for a wide circle of people interested in the culture of the Polish and Czech nations. In this lies the main importance of the work The Slavic Literature Translations, which is a very interesting work in Poland. Key words: Commentary, bibliography, translation, Polish and Czech literature.